9(x-4)+x=10(x-4)+4

Simple and best practice solution for 9(x-4)+x=10(x-4)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-4)+x=10(x-4)+4 equation:


Simplifying
9(x + -4) + x = 10(x + -4) + 4

Reorder the terms:
9(-4 + x) + x = 10(x + -4) + 4
(-4 * 9 + x * 9) + x = 10(x + -4) + 4
(-36 + 9x) + x = 10(x + -4) + 4

Combine like terms: 9x + x = 10x
-36 + 10x = 10(x + -4) + 4

Reorder the terms:
-36 + 10x = 10(-4 + x) + 4
-36 + 10x = (-4 * 10 + x * 10) + 4
-36 + 10x = (-40 + 10x) + 4

Reorder the terms:
-36 + 10x = -40 + 4 + 10x

Combine like terms: -40 + 4 = -36
-36 + 10x = -36 + 10x

Add '36' to each side of the equation.
-36 + 36 + 10x = -36 + 36 + 10x

Combine like terms: -36 + 36 = 0
0 + 10x = -36 + 36 + 10x
10x = -36 + 36 + 10x

Combine like terms: -36 + 36 = 0
10x = 0 + 10x
10x = 10x

Add '-10x' to each side of the equation.
10x + -10x = 10x + -10x

Combine like terms: 10x + -10x = 0
0 = 10x + -10x

Combine like terms: 10x + -10x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 | | -47.62=k+89.2 | | 2x^2+22x+54=0 | | (7+3y)2= | | 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x |

Equations solver categories